Sistem Otomatisasi Pengolahan Tambak Udang dengan Pengaturan Sirkulasi Air, Ketinggian dan Pemberian Pakan Terintegrasi Internet Of Things - Juanda; Muhammad Zenny Prananda; Surya Fajar Siddiq; Syahada Sabanu; David JM Sembiring; Sri Novida Sari (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2023)
Checking the quality of water that is not periodic or continuous, this can result in sudden changes in water quality without the shrimp farmers noticing so that it has a negative impact on the shrimp cultivation process and results in crop failure. To achieve optimal production targets, good management is needed, such as choosing the right location, pond design and construction, proper pond preparation, water preparation, seed selection and stocking, water management, feed management, and harvesting. Therefore, it is necessary to increase application of innovative, applicable and efficient technology, as an effort to increase pond productivity and improve environmental quality.